2015
DOI: 10.3923/ajcs.2015.160.173
|View full text |Cite
|
Sign up to set email alerts
|

GGE Biplot Analysis for Combining Ability of Grain Yield and Early Maturity in Maize Mutant in Indonesia

Abstract: Determination of combining abilities and heterotic groupings of parental lines is very important in selecting the mutant lines and to decide breeding strategies for maize hybrid production. Fourty six new mutant lines used in maize breeding programs in Indonesia, were crossed to three tester lines in a lines×testers mating design. The 138 F1 hybrids, the 46 parental lines and 3 tester lines were evaluated at Arjasari, West Java, Indonesia for the following objectives: (i) to analyze line×tester data for maturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The genotype + genotype × environment (GGE) biplot analysis is the main method to demonstrate the combining abilities of parents and crosses. Thus, this method has commonly been used to evaluate combining abilities in maize breeding experiments in recent years (Mostavi et al, 2012;Badu-Apraku et al, 2013;Ruswandi et al, 2015). Additionally, the canonical discriminant analysis with yypothesis error (CDA-HE) plot has also been used to evaluate genotypes in breeding experiments for investigated traits (Egesel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The genotype + genotype × environment (GGE) biplot analysis is the main method to demonstrate the combining abilities of parents and crosses. Thus, this method has commonly been used to evaluate combining abilities in maize breeding experiments in recent years (Mostavi et al, 2012;Badu-Apraku et al, 2013;Ruswandi et al, 2015). Additionally, the canonical discriminant analysis with yypothesis error (CDA-HE) plot has also been used to evaluate genotypes in breeding experiments for investigated traits (Egesel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the SCA effects are attributed to the differences in the heterotic potential of different cross combinations and differences in the genetic background of the genotypes. Ruswandi et al (2015) also observed the SCA effects of lines for different agronomic traits of maize using GGE biplot analysis for line × tester data and found that different lines were having different SCA effects for different traits.…”
Section: Discussionmentioning
confidence: 99%
“…It was evident that T5 (14966) was average tester for PVAC and YPH among studied five different testers. Ruswandi et al (2015) also visualized the average testers for different agronomic traits of maize using GGE biplot analysis for line × tester data and found that different testers were average testers for different traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GGE biplot has extensively been used to study the GCA and SCA in a cross and identifying best cross combinations for diallel data (Anido et al 2004;Bertoia et al 2006;Darvishzadeh et al 2009;Vivek et al 2010). But such studies have been less done for line × tester data (Fotokian and Agahi 2014;Kahriman et al 2016;Kannababu et al 2017;Ruswandi et al 2015).…”
Section: Introductionmentioning
confidence: 99%